2020
DOI: 10.1101/2020.10.15.20213025
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic review on chronic non-communicable disease in disaster settings

Abstract: Background: Non-communicable diseases (NCDs) constitute the leading cause of mortality globally. Low and middle-income countries (LMICs) not only experience the largest burden of humanitarian emergencies but are also disproportionately affected by NCDs, yet primary focus on the topic is lagging. We conducted a systematic review on the effect of humanitarian disasters on NCDs in LMICs assessing epidemiology, interventions, and treatment. Methods: A systematic search in MEDLINE, MEDLINE (PubMed, for in-process … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 87 publications
(298 reference statements)
0
11
0
Order By: Relevance
“…Lengthy electrical outages (in addition to adverse living conditions) were also widely reported by participants as severely affecting mental health and presenting signi cant long-term challenges for the refrigeration of medicines like insulin and operation of medical equipment. While the effects of power outages on individuals with NCDs has been described in other studies, the extent and duration of these interruptions following Hurricane Maria far surpassed those previously reported, and the implications of long-term power outages for individuals with NCDs, including considerations of fuel supply su ciency to power generators and mental health consequences, has not been adequately described in the literature (47,69,103,105,106). This nding is particularly relevant to communities throughout the U.S. with aging infrastructure, including electrical grids.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Lengthy electrical outages (in addition to adverse living conditions) were also widely reported by participants as severely affecting mental health and presenting signi cant long-term challenges for the refrigeration of medicines like insulin and operation of medical equipment. While the effects of power outages on individuals with NCDs has been described in other studies, the extent and duration of these interruptions following Hurricane Maria far surpassed those previously reported, and the implications of long-term power outages for individuals with NCDs, including considerations of fuel supply su ciency to power generators and mental health consequences, has not been adequately described in the literature (47,69,103,105,106). This nding is particularly relevant to communities throughout the U.S. with aging infrastructure, including electrical grids.…”
Section: Discussionmentioning
confidence: 84%
“…Remote communities with mountainous terrain experienced the greatest impact from these shortages due to extended road blockages that created additional delays in procurement. While there are studies that have reported the impact of medication shortages on individuals with NCDs, there are less studies that have reported similar ndings related to oxygen supplies (12,44,45,47,70,(103)(104)(105)110,111). Many current patient guidelines recommend storing a 3-7-day supply of medications and inform patients about prescription assistance programs, which require access to internet or telephone (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our aim is to guide allocation of resources, future research, and intervention development. The full systematic review is published elsewhere [15].…”
Section: Introductionmentioning
confidence: 99%